STEREOTACTIC MANAGEMENT OF COLLOID CYSTS OF 3RD VENTRICLE - Shams, Shahzad; Butt, Rizwan Masood; Ahmed, Nazir (Journal of Ayub Medical College Abbottabad, 1996)
Stereotactic aspiration is a valuable surgical alternative for colloid cysts. From Oct 1994 to Oct 1995, 5 patients had computerized tomography-guided stereotactic removal of colloid cysts. Leksell CT compatible stereotactic frame was used with complete removal in 2 and partial removal in 3 cases. Volume of colloid material removed ranged from 3-6 ml. Average time spent in hospital was 7 days. No mortality and minimal morbidity was seen. There is no evidence of recurrence in average follow up of 8 months. Stereotactic removal of colloid cysts is safe and provides a new option for management of colloid cysts.